2010
DOI: 10.1007/s11109-010-9151-8
|View full text |Cite
|
Sign up to set email alerts
|

Electoral Competitiveness and Issue Voting

Abstract: This article suggests that voters rely more strongly on ''substantial'' criteria, such as issues and ideology, when elections are competitive. In such contexts, voters should attach more importance to their own choice and rely less on ''heuristics.'' Three aspects of election competitiveness are considered: the fragmentation and polarization of the party system and the proportionality of the electoral system. Elections are more competitive when there are many parties in competition, when they differ strongly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…In line with recent work on the cognitive basis of electoral behavior (e.g. Kriesi 2005; Mondak et al 2010;Lachat 2011;Nai 2014a) we expect those conditions to be found both at the individual and information environment level. At the individual level, we argue that political knowledge positively affects consistent decisions.…”
Section: Introductionsupporting
confidence: 85%
“…In line with recent work on the cognitive basis of electoral behavior (e.g. Kriesi 2005; Mondak et al 2010;Lachat 2011;Nai 2014a) we expect those conditions to be found both at the individual and information environment level. At the individual level, we argue that political knowledge positively affects consistent decisions.…”
Section: Introductionsupporting
confidence: 85%
“…Voters develop easy ways to make up their minds. Rather than engaging in a rational comparison of the parties’ various positions with their own preferences, they rely on simpler decision‐making strategies called heuristics (Lachat, ) or shortcuts. Heuristics are easily available pieces of information that allow for decision making without processing a huge amount of information.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Voters, for their part, purportedly hold representatives more accountable (Canes-Wrone, Brady and Cogan, 2002), turn out to vote in greater numbers (Powell, 1986;Selb, 2009) and weigh both incumbent performance (Koch, 1998) and issues (Lachat, 2011) more when elections are competitive. In combination with other innovations in political measurement, theoretically important relationships can also be tested for the first time cross-nationally.…”
mentioning
confidence: 99%